Experimental observation of a dissipative phase transition in a multi-mode many-body quantum system - Benary, J.; Baals, C.; Bernhart, E.; Jiang, J.; Roehrle, M.; Ott, Herwig (New Journal of Physics, 2022)
Dissipative phase transitions are a characteristic feature of open systems. One of the paradigmatic examples for a first order dissipative phase transition is the driven nonlinear single-mode optical resonator. In this work, we study a realization with an ultracold bosonic quantum gas, which generalizes the single-mode system to many modes and stronger interactions. We measure the effective Liouvillian gap of the system and find evidence for a first order dissipative phase transition. Due to the multi-mode nature of the system, the microscopic dynamics is much richer and allows us to identify a non-equilibrium condensation process.
CRIS-Team Scopus Importer:2023-03-27
Keywords: dissipative phase transitions; open quantum systems; quantum gases